ANALISIS PERTUMBUHAN ENDOGEN DALAM OTONOMI DAERAH - Bambang Ismawan (Journal of Indonesian Economy and Business (JIEB), 2003)
Decentralization era is a momentum for mobilizing local resources to develop localcapital. Microfinance is the key to capital formation at the local level, solve the bigproblem of poverty and empower people’s socio economy. The strength of microfinance is based on people driven and it’s sustainability. Microfinance will contribute broad based development and development through equity.Keywords: Accessibility, people’s economy, self reliance, microfinance, microenterprise, sustainability